Homologies between enzymes involved in steroid and xenobiotic carbonyl reduction in vertebrates, invertebrates and procaryonts. - Oppermann, U; Maser, E; Hermans, J; Koolman, J; Netter, K (1992)
Evidence is reported for the existence of a structurally and functionally related and probably evolutionarily conserved class of membrane-bound liver carbonyl reductases/hydroxysteroid dehydrogenases involved in steroid and xenobiotic carbonyl metabolism. Carbonyl reduction was investigated in liver microsomes of 8 vertebrate species, as well as in insect larvae total homogenate and in purified 3 alpha-hydroxysteroid dehydrogenase preparations of the procaryont Pseudomonas testosteroni, using the ketone compound 2-methyl-1,2 di-(3-pyridyl)-1-propanone (metyrapone) as substrate. The enzyme activities involved in the metyrapone metabolism were screened for their sensitivity to several steroids as inhibitors. In all fractions tested, steroids of the adrostane or pregnane class strongly inhibited xenobiotic carbonyl reduction, whereas only in the insect and procaryotic species could ecdysteroids inhibit this reaction. Immunoblot analysis with antibodies against the respective microsomal mouse liver metyrapone reductase revealed strong crossrections in all fractions tested, even in those of the insect and the procaryont. A similar crossreaction pattern was achieved when the same fractions were incubated with antibodies against 3 alpha-hydroxysteroid dehydrogenase from Pseudomonas testosteroni. The mutual immunoreactivity of the antibody species against proteins from vertebrate liver microsomes, insects and procaryonts suggests the existence of structural homologies within these carbonyl reducing enzymes. This is further confirmed by limited proteolysis of purified microsomal mouse liver carbonyl reductase and subsequent analysis of the peptide fragments with antibodies specifically purified by immunoreactivity against this respective crossreactive antigen. These immunoblot experiments revealed a 22 kDa peptide fragment which was commonly recognized by all antibodies and which might represent a conserved domain of the enzyme.